CONSEPTUAL METAPHORS AS MEDIATORS OF THE AUTHOR’S INDIVIDUAL WORLD-PICTURE - Khamroyeva Shakhzoda Ikromovna (Scholar Express Journal, 2025)
Conceptual metaphors serve as fundamental cognitive tools that shape human thought, communication, and artistic expression. In literary and linguistic studies, they function not merely as stylistic embellishments but as essential frameworks through which authors construct meaning. This paper explores the role of conceptual metaphors in shaping authorial worldviews, analyzing their linguistic manifestations and cognitive implications. Drawing on Lakoff and Johnson’s Conceptual Metaphor Theory (1980), the study examines how metaphors transcend decorative language to influence narrative structure, thematic development, and ideological positioning. Through textual analysis of literary and philosophical works, the research demonstrates that conceptual metaphors are indispensable in decoding an author’s unique perspective
Keywords: conceptual metaphor; cognitive linguistics; authorial worldview